The highest bidder : a citizen's guide to problems of foreign investment in Australia - Fitzpatrick, Brian; Wheelwright, E. L. (Melbourne : Lansdowne : [London, Newness, 1965)
This book provides basic information on overseas investment as it relates Australia's economy. It examines the policy of unrestricted entry of foreign capital in the economy and its attendant dangers.
Includes bibliographic footnotes and index
usc 11/06/2018
Loans
Keywords: Investments, Foreign